Pengaruh Gaya Belajar Siswa dan Pola Asuh Anak dalam Keluarga terhadap Hasil Belajar Matematika Siswa Kelas XI di SMA Islam YMI Wonopringgo Kabupaten Pekalongan - Albar, Ardian Shafry; Pramesti, Santika Lya Diah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Learning outcomes are an achievement that students produce through a learning process. Learning outcomes can be influenced by several factors, namely student learning styles and their upbringing in the family. The purpose of this study was to determine how much the learning styles and parenting styles of students affected the mathematics learning outcomes of students at SMA Islam YMI Wonopringgo, Pekalongan Regency. This research is a quantitative research. Collecting data using questionnaires and documentation. The data analysis technique used multiple linear regression analysis. From the results of the research test, it was found that the coefficient of determination R2 of the student learning style variable had an effect on student learning outcomes by 29.1%. Then the test results of the coefficient of determination R2 of the variable parenting style in the family have an effect on student learning outcomes by 19.4%. As well as the test results of the coefficient of determination R2 variable student learning styles and parenting in the family have an effect on student learning outcomes by 32.7%.